2018
DOI: 10.1007/s11095-018-2371-z
|View full text |Cite
|
Sign up to set email alerts
|

‘In Vitro’, ‘In Vivo’ and ‘In Silico’ Investigation of the Anticancer Effectiveness of Oxygen-Loaded Chitosan-Shelled Nanodroplets as Potential Drug Vector

Abstract: Due to their intrinsic toxicity OLN might be considered an adjuvant tool suitable to deliver their therapeutic cargo intracellularly and may be proposed as promising combined delivery system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Chitosan NPs exhibit outstanding biodegradable and biocompatible properties, and for these reasons they are extensively studied as drug carriers. Studies have shown that chitosan NPs can deliver many drugs, including genes, proteins [66,67,68], anticancer chemical drugs [69,70], and antibiotics [71,72]; and via various routes of administration, including oral, nasal, intravenous, and ocular [73,74,75]. CS–TPP NPs have been investigated for the delivery of anticancer and protein drugs by oral administration [76,77,78].…”
Section: Polysaccharide Are Commonly Investigated As Nanoparticulamentioning
confidence: 99%
“…Chitosan NPs exhibit outstanding biodegradable and biocompatible properties, and for these reasons they are extensively studied as drug carriers. Studies have shown that chitosan NPs can deliver many drugs, including genes, proteins [66,67,68], anticancer chemical drugs [69,70], and antibiotics [71,72]; and via various routes of administration, including oral, nasal, intravenous, and ocular [73,74,75]. CS–TPP NPs have been investigated for the delivery of anticancer and protein drugs by oral administration [76,77,78].…”
Section: Polysaccharide Are Commonly Investigated As Nanoparticulamentioning
confidence: 99%
“…The production of nanocarriers is one the most innovative and promising research fields in modern pharmaceutical technology: As a matter of fact, the use of nanoscale formulations can improve drug compatibility [1,2], provide more accurate diagnosis [3,4], reduce the risk of immune response [5,6], and achieve targeted drug delivery [7,8]. Despite the aforementioned scientific advancements, the market of nanoscale medical devices is still a niche one, not only because of regulatory issues, but also because of the difficulties encountered in producing nanocarriers at an industrial scale [9].…”
Section: Introductionmentioning
confidence: 99%
“…Various NDs with polymer shells have been fabricated with the development of polymer materials. The most often used polymer materials include natural polymers such as chitosan [7,8] and alginate [9], as well as synthetic block polymer materials such as poly (ethylene glycol)-block-Poly (ε-caprolactone) (PEG-PCL) [10,11]. Due to the stability and stiffness of the shell, polymeric NDs usually have a higher cavitation threshold and longer circulation time than lipid NDs [12].…”
Section: The Shells Of Ndsmentioning
confidence: 99%